A review on the application of blog, blogger, widget and hypertext to develop a web-based instructional tool - Mah, Boon Yih; Ab Rahim, Suzana (Journal of English Language Teaching Innovations and Materials (Jeltim), 2019)
The use of the internet for teaching and learning has become a global trend among the education practitioners over the recent decades. The integration of technology and media into Malaysian English as a Second Language (ESL) classrooms has altered the methods in English Language Teaching (ELT). In response to the impact of technology in ELT, the needs of a supplementary instructional platform, and the limitations of the learning management system (LMS) in fostering second language (L2) writing skill, a web-based instructional tool was designed and developed based on a theoretical-and-pedagogical framework namely Web-based Cognitive Writing Instruction (WeCWI). To determine the key concepts while identifying the research gap, this study conducted a literature review using online search on specific keywords including “blog”, “Blogger”, “widget”, and “hyperlink” found in the scholarly articles. Based on the review of literature, Blogger was opted due to its on-screen customisable layout editing features that can be embedded with web widgets and hypertext that share the identical features. By looking into the relationship between perceptual learning preferences on perceived information and the visual representations in iconic and symbolic views, the blogs can come with two different user interfaces embedded with web widgets or hypertext. The blog with web widgets appears in a graphical form of iconic view; while hypertext only displays textual form of symbolic view without involving the visual references. With the injection of web widgets and hypertext into the blogs, WeCWI attempts to offer a technological enhanced ELT solution to overcome the poor writing skill with a better engagement while learning online through the learners’ preferred perceptual learning preferences.